Alpha activity and cardiac correlates: three types of relationships during nocturnal sleep - Ehrhart, J; Toussaint, M; Simon, C; Gronfier, C; Luthringer, R; Brandenberger, G (Clinical neurophysiology, 2000)
Objective: We examined simultaneously alpha activity and cardiac changes during nocturnal sleep, in order to differentiate non-rapid eye movement (NREM) sleep, REM sleep, and intra-sleep awakening. Methods: Ten male subjects displaying occasionally spontaneous intra-sleep awakenings underwent EEG and cardiac recordings during one experimental night. The heart rate and heart rate variability were calculated over 5 min periods. Heart rate variability was estimated: (1) by the ratio of low frequency (LF) to high frequency (HF) power calculated from spectral analysis of R-R intervals; and (2) by the interbeat autocorrelation coefficient of R-R intervals (rRR). EEG spectral analysis was performed using a fast Fourier transform algorithm. Results: Three types of relationships between alpha waves (8–13 Hz) and cardiac correlates could be distinguished. During NREM sleep, alpha activity and cardiac correlates showed opposite variations, with high levels of alpha power associated with decreased heart rate, rRR and LF/HF ratio, indicating low sympathetic activity. Conversely, during REM sleep, alpha activity was low whereas heart rate, rRR, and the LF/HF ratio peaked, indicating high sympathetic activity. During intra-sleep awakenings, alpha activity and cardiac correlates both increased. No difference in time-course between alpha 1 (8–10 Hz) and alpha 2 (10–13 Hz) activity could be shown. Alpha waves occurred in fronto-central areas during slow wave sleep (SWS), migrated to posterior areas during REM sleep, and were localized in occipital areas during intra-sleep awakenings. Conclusions: These results suggest that alpha waves are not simply a sign of arousal, as is commonly thought. Fronto-central alpha waves, associated with decreased heart rate, possibly reflect sleep-maintaining processes.